A escuta da Palavra de Deus proclamada na liturgia: um desafio em “tempos líquidos” - Quirino, Ademilson Tadeu (2017)
The present research aims to introduce some elements of deep relevance to better understand the importance of listening to the word of God proclaimed in the liturgy, "in liquid times". This expression, regarded by the Polish sociologist Zygmunt Bauman liquid Modernity and works While liquids, translates one of the great challenges to make satisfying about listening. A pedagogical perspective, is reflected, first, about the bug as liturgical principle operating in the human person-in physiological and metaphorical sense, until you reach the Shema Israel (Dt 4.6) and Fides ex auditu (Rm 10.17) paulino. Hence if paves the way for weights about the word of God heard in the liturgy, with biblical-theological grounds of listening to the word of God in the law, in some assemblies of the people of Israel, to the understanding of listening to the word of God in the liturgical assemblies today encourages the Ecumenical Council Vatican II, Sacrosanctum Concilium and constitutions Dei Verbum, without losing sight of some fathers of the Church and the Magisterium. On this basis, some challenges and lights are pointed to the need for a culture of listening, so that, in the silence of words, the word of God proclaimed in the liturgy, has primacy and be experienced in a practical way. For that, in modern society, in which live the culture of noises, you should focus on celebrating space as environment of silence and listening. Visa so awakening in the heart of the listener, through gestures and words, the sacramental dimension of Scripture in the liturgy, in a dynamic perspective, ritual, and experiential mystagogical pedagogical, leading to your full effectiveness